2015
DOI: 10.1017/s0950268815000771
|View full text |Cite
|
Sign up to set email alerts
|

The East Jakarta Project: surveillance for highly pathogenic avian influenza A(H5N1) and seasonal influenza viruses in patients seeking care for respiratory disease, Jakarta, Indonesia, October 2011–September 2012

Abstract: Indonesia has reported the most human infections with highly pathogenic avian influenza (HPAI) A(H5N1) virus worldwide. We implemented enhanced surveillance in four outpatient clinics and six hospitals for HPAI H5N1 and seasonal influenza viruses in East Jakarta district to assess the public health impact of influenza in Indonesia. Epidemiological and clinical data were collected from outpatients with influenza-like illness (ILI) and hospitalized patients with severe acute respiratory infection (SARI); respira… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 26 publications
1
17
0
Order By: Relevance
“…Very few physicians reported ever diagnosing a patient with pandemic influenza or with suspected HPAI H5N1 in either outpatients or hospitalized patients. A recent one‐year surveillance study reported that 15.5% of hospitalized patients with severe acute respiratory infection (SARI) tested positive for influenza viruses, including 36% during weeks of peak influenza activity in East Jakarta District, Jakarta, Indonesia . Together with our findings, this suggests that Indonesian clinicians need to be educated further about the potential for influenza to cause severe illness resulting in hospitalization.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…Very few physicians reported ever diagnosing a patient with pandemic influenza or with suspected HPAI H5N1 in either outpatients or hospitalized patients. A recent one‐year surveillance study reported that 15.5% of hospitalized patients with severe acute respiratory infection (SARI) tested positive for influenza viruses, including 36% during weeks of peak influenza activity in East Jakarta District, Jakarta, Indonesia . Together with our findings, this suggests that Indonesian clinicians need to be educated further about the potential for influenza to cause severe illness resulting in hospitalization.…”
Section: Discussionsupporting
confidence: 74%
“…Together with our findings, this suggests that Indonesian clinicians need to be educated further about the potential for influenza to cause severe illness resulting in hospitalization. Additionally, physicians should be educated on the value of surveillance data to better understand when seasonal influenza viruses are circulating and on the burden of seasonal influenza in Indonesia, such as the results of ongoing enhanced influenza surveillance among SARI patients …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Three of these papers were based on ILI surveillance of multiple seasons, reporting a proportion of type B viruses between 25.4% and 36% among all influenza‐positive samples during the overall study period . Two papers provided season‐specific information on the proportion of influenza B among all ILI cases with laboratory‐confirmed influenza in 2010‐11 and 2011‐12 . One of them also provided data in SARI patients with laboratory‐confirmed influenza in 2011‐12.…”
Section: Resultsmentioning
confidence: 99%
“…In that study, the influenza detection rate was higher among ILI than among SARI patients (34.5% vs 15.4%). In both patient groups, 47% of laboratory‐confirmed influenza cases were influenza B …”
Section: Resultsmentioning
confidence: 99%